(untitled) (Journal of the College of Education for Women, 2022)
The aim of the research is to reveal the reality of teacher performance evaluation in the Sultanate of Oman in light of some global models. The study followed a qualitative descriptive research design. Seven forms of teacher formative and summative assessments were analyzed. Besides, an analytical template was developed, consisting of six areas related to the teaching performance of teachers. These included: lesson planning and preparation, learning environment, education, professional development, student academic, and community and parental partnership. The study reached a number of results; the most notable is the lack of change of forms for more than a decade despite the rapid development of the educational system in the sultanate in areas close to the teacher. It has also found that the formative evaluation focuses only on his/her rile in the classroom, such as lesson planning, preparation and learning environment. Further, it does not focus on his/her role outside the classroom, such as professional development, and community and parental partnership. Additionally, this evaluation is not based on any professional standards. Therefore, its tools, standards, and assessment need to be improved. The study has also shown that the final evaluation needs do not have sufficient standards. Additionally, both types of assessments do not relate to each other. Based on these results, the study has recommended to improve teacher performance evaluation in the Sultanate of Oman.